2022
DOI: 10.21203/rs.3.rs-2007212/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Response of cotton genotypes to water-deficit stress using drought tolerance indices and principal component analysis

Abstract: Background Drought impacts on cotton cultivation and production are expected to worsen as a result of global warming and water-deficit stress. Drought tolerance indices and PCA analysis were used to evaluate drought stress responses in eleven cotton genotypes and fifteen indices' ability to identify drought-tolerant genotypes under normal and drought circumstances. Results Seed cotton yield (Kentar/Feddan) was significantly affected by genotypes, years, and their interaction (p ≤ 0.05 or 0.01) under normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…The HM index revealed that the G15, G16, G19, G3 and G7 are heat tolerant, while the G23, G21 and G12 were identified as heat-sensitive genotypes. Our results were in agreement with the findings of (Yehia, 2020). The G15, G16, G3, G19 and G7 exhibited higher STI index values and were declared heat resistant and high yield genotypes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The HM index revealed that the G15, G16, G19, G3 and G7 are heat tolerant, while the G23, G21 and G12 were identified as heat-sensitive genotypes. Our results were in agreement with the findings of (Yehia, 2020). The G15, G16, G3, G19 and G7 exhibited higher STI index values and were declared heat resistant and high yield genotypes.…”
Section: Discussionsupporting
confidence: 92%
“…The SSI index showed that the G7, G21, G15 and G8 were the most heat tolerant genotypes, whereas the G12, G14, G2, G17 and G5 were the most heat susceptible genotypes. Different studies suggested that SSI is used to determine stress-tolerant cotton genotypes (Anwar et al, 2011;Yehia, 2020). The SSI recognizes only those cultivars having the least differences under normal and stress conditions (Fischer and Maurer, 1978).…”
Section: Discussionmentioning
confidence: 99%